Kualitas Fisik Dan Kandungan TDN Dari Rumput BD (Brachiaria decumbens) Yang Diberi Pupuk Kotoran Kelinci Dengan Dosis Berbeda - Putu Aditya Febryandika Permana; Ni Ketut Etty Suwitari; I Gusti Ayu Dewi Seri Rejeki (GEMA AGRO, 2025)
Brachiaria decumbens grass is a high-quality forage that can grow well in tropical regions and has great potential in improving the efficiency of ruminant livestock production. This research aims to determine the effect of rabbit manure fertilizer on the physical quality and Total Digestible Nutrients (TDN) content of Brachiaria decumbens grass, as well as to determine the best dosage for its application. The research was conducted using a Randomized Block Design (RBD) with five treatments: P0 (without fertilizer), P1 (10 tons/ha), P2 (20 tons/ha), P3 (30 tons/ha), and P4 (40 tons/ha), each with three replications. The observed variables included bulk density, water solubility, water absorption, TDN, and gross energy. The analysis results showed that the application of rabbit manure fertilizer had a very significant effect (P<0.01) on water solubility and water absorption, and a significant effect (P<0.05) on bulk density. Treatment P4 produced the best values with the lowest bulk density (231.28 g/cm³), highest water absorption (10.47%), and lowest water solubility (25.51%). Although the TDN and gross energy values were not significantly different (P>0.05), both showed an increasing trend, reaching 24.34% and 3.61 kcal/g respectively in treatment P4. These results indicate that the application of rabbit manure fertilizer can improve the physical quality and tends to increase the nutritional value of the grass. A dosage of 40 tons/ha is recommended as the optimal treatment for sustainable cultivation of Brachiaria decumbens grass